PHYSICAL EXERCISE AND ITS IMPLICATIONS ON COGNITIVE FUNCTION: A SYSTEMATIC REVIEW (Fiep Bulletin - online, 2011)
The present study is concerned to the relation between social mobility and the adoption of forms of leisure. Above all, it is based on the life conditions to which children are exposed in current society and searches for the relation with forms of leisure they make use of in order to achieve their own distraction and/or satisfaction. The cornerstone of this study is the reflection over these problems in relation to the process of social mobility, but also included in the process of cultural mobility. In order to attain this goal, the possible connection between social mobility and sedentariness issues and their derivatives is analyzed, as well as the connection between quality of life and different cultures of leisure.
Keywords: social mobility; leisure; access